Study guides

☆☆

Q: What is the factorization of 4x2 plus 6x plus 2?

Write your answer...

Submit

Still have questions?

Related questions

2(x + 1)(2x + 1)

2(4x2 + 6x - 1)

-4x2 + 11x - 6 factors to: (-4x + 3) (x - 2)

4x2(x2-7x+10) 4x2(x-2)(x-5)

4x2 - 6x - 12 = 2 (2x2 - 3x - 6) There are no integer roots, the approximate roots are 2.64 and -1.14

5x2-2x+16=4x2+6x ,or x2-8x+16=0, or x2-2(x)(4)+(4)2=0, or (x-4)2=0, or (x-4)(x-4)=0, or x=4

4x2 - 12x + 9 = 4x2 - 6x - 6x + 9 = 2x(2x - 3) - 3(2x - 3) = (2x - 3)(2x - 3) or (2x - 3)2

Y = 4x2 + 6x - 1Use the pq-formula:x = -4/2 +- sqrt ((4/2)2 -(-1))x = -2 +- sqrt((16/4) +1)x = -2 +- sqrt(4 +1)x1 = -2 + sqrt(5)x2 = -2 - sqrt(5)

(6x^5-4x^2)+(2x^3-3) = 6x^5-4x^2+2x^3-3 The grestest exponent is 5, which is the degree of the above expression.

5x^2 + 6x - 2 doesn't factor neatly. Applying the quadratic formula, we find two real solutions: (-3 plus or minus the square root of 19) divided by 5. x = 0.2717797887081348 x = -1.4717797887081348

-4x2 + 6x + 40 = 0 ∴ -2x2 + 3x + 20 = 0 ∴ -2x2 - 8x + 5x + 20 = 0 ∴ -2x(x + 4) + 5(x + 4) = 0 ∴ (5 - 2x)(x + 4) = 0 ∴ x ∈ {5/2, -4}

It is: -4x^2 +11x -6 equals (-4x+3)(x-2) when factored

People also asked